2016
DOI: 10.17796/1053-4628-40.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Occurrence of Distoclusion in the Primary Dentition: A Hierarchical Analysis

Abstract: Counseling with regard to the duration of pacifier use could contribute toward reducing the prevalence of distoclusion and its consequences in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
3
7
0
5
Order By: Relevance
“…Socioeconomic variables were not associated with malocclusion in the primary dentition. Similar results were reported in previous studies using other indicators, such as maternal schooling, 11,30 family structure, monthly household income, 30 and socioeconomic status. 4 Such comparisons however require caution due to the use of different variables for socioeconomic characterisation of the families.…”
Section: Discussionsupporting
confidence: 91%
“…Socioeconomic variables were not associated with malocclusion in the primary dentition. Similar results were reported in previous studies using other indicators, such as maternal schooling, 11,30 family structure, monthly household income, 30 and socioeconomic status. 4 Such comparisons however require caution due to the use of different variables for socioeconomic characterisation of the families.…”
Section: Discussionsupporting
confidence: 91%
“…and Agarwal et al . 13, 14, 32, 33 investigated the same association in primary dentition. The relationship between breastfeeding and the development of occlusion/malocclusion was analyzed in nine studies, all in primary dentition 57, 1012, 18, 34, 35 .…”
Section: Resultsmentioning
confidence: 95%
“…Some of the authors who examined the relationship between breastfeeding and dental class II found that a longer period of breastfeeding was associated with less prevalence of this class of malocclusion in mixed dentition 31 and in primary dentition 13, 14, 32 However, no relationship between class II and breastfeeding was found by Luz et al . 30 in mixed dentition or by Karjalainen et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations